2013
DOI: 10.1097/ana.0b013e31829795ce
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Elevated Intracranial Pressure through Noninvasive Methods

Abstract: Elevated intracranial pressure (ICP) is an important cause of secondary brain injury, and a measurement of ICP is often of crucial value in neurosurgical and neurological patients. The gold standard for ICP monitoring is through an intraventricular catheter, but this invasive technique is associated with certain risks. Intraparenchymal ICP monitoring methods are considered to be a safer alternative but can, in certain conditions, be imprecise due to zero drift and still require an invasive procedure. An accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 92 publications
(150 reference statements)
2
129
0
21
Order By: Relevance
“…However, sustained hyperventilation can decrease CBF, resulting in poor prognosis in patients with elevated ICP [19]. Non-invasive monitoring technique such as sonographic ONSD measurement can be promptly applied and performed at bedside to evaluate ICP [9,21] and may help to make optimal strategy in ICP management. Even though patients included in this study did not suffer from intracranial lesion and had normal brain compliance, ONSD showed a significant response in associated CO 2 change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sustained hyperventilation can decrease CBF, resulting in poor prognosis in patients with elevated ICP [19]. Non-invasive monitoring technique such as sonographic ONSD measurement can be promptly applied and performed at bedside to evaluate ICP [9,21] and may help to make optimal strategy in ICP management. Even though patients included in this study did not suffer from intracranial lesion and had normal brain compliance, ONSD showed a significant response in associated CO 2 change.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct ICP measurement technique such as ventriculostomy is known as a standard, it is invasive and difficult to apply as routine monitoring of all patients likely to experience increased ICP, even in critically ill patients. Sonographic measurement of ONSD is a non-invasive technique and has been reported to provide a good association with ICP [21,28,29]. Thus, ONSD can be a good alternative in predicting ICP increase without risk of infection or bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of an external ventricular drain is the preferred method to monitor ICP, particularly in the setting of hydrocephalus [6]. Noninvasive devices do not reliably quantify ICP [46]. However, they may be used to estimate ICP when invasive monitoring is not feasible, along with information from imaging [47][48][49].…”
Section: Intracranial and Cerebral Perfusion Pressure Monitoringmentioning
confidence: 99%
“…Among them are intraocular pressure assessment [2], tympanic membrane displacement [3], ultrasonography [4,5] and measurement of intracranial blood flow [6][7][8][9]. In the individual, these methods have shown a fairly high correlation between non-invasive and invasive ICP assessments (Table 1).…”
Section: Introductionmentioning
confidence: 97%